PENDIDIKAN DAN PELATIHAN MITIGASI BENCANA GEMPA PADA SANTRIWATI DI PONPES DARU ABDILLAH TANJUNGSARI BOYOLANGU TULUNGAGUNG - Hendra Pratama (BHAKTI: JURNAL PENGABDIAN DAN PEMBERDAYAAN MASYARAKAT, 2025)
Traditional Islamic boarding schools (pesantren) generally do not provide disaster mitigation education, as they focus more on religious teachings that emphasize the values of monotheism, sincerity, and surrender to Allah SWT. These values shape the students' mentality to remain steadfast and not panic when facing disasters. This community service-based research uses the Service Learning method to improve female students' understanding and knowledge of disasters and mitigation skills through earthquake disaster simulations. This participatory approach actively involves female students in the learning process, risk identification, disaster simulation, and evacuation. The aim of this study is to equip female students with preparedness skills in facing disasters by combining the strength of religious values, knowledge, and direct mitigation simulations. The research was conducted at Pondok Pesantren Daru Abdillal, Tanjungsari, Boyolangu, Tulungagung.